Sticking points: common‐agency problems and contracting in the US healthcare system. (1st April 2019) - Frandsen, Brigham; Powell, Michael; Rebitzer, James B.
Abstract: We propose a "common‐agency" model for explaining inefficient contracting in the US healthcare system. Common‐agency problems arise when multiple payers seek to motivate a provider to invest in improved care coordination. We highlight the possibility of "sticking points, " that is, Pareto‐dominated equilibria in which payers coordinate around contracts which give weak incentives to the provider. Sticking points rationalize three hard‐to‐explain features of the US healthcare system: widespread fee‐for‐service arrangements; problematic care coordination; and the historical reliance on single‐specialty practices to deliver care. The model also analyzes the effects of policies promoting more efficient contracting between payers and providers.